IL-7 receptor blockade blunts antigen-specific memory T cell responses and chronic inflammation in primates. Issue 1 (December 2018) - Belarif, Lyssia; Mary, Caroline; Jacquemont, Lola; Mai, Hoa; Danger, Richard; Hervouet, Jeremy; Minault, David; Thepenier, Virginie; Nerrière-Daguin, Veronique; Nguyen, Elisabeth; Pengam, Sabrina; Largy, Eric; et al.
Abstract Targeting the expansion of pathogenic memory immune cells is a promising therapeutic strategy to prevent chronic autoimmune attacks. Here we investigate the therapeutic efficacy and mechanism of new anti-human IL-7Rα monoclonal antibodies (mAb) in non-human primates and show that, depending on the target epitope, a single injection of antagonistic anti-IL-7Rα mAbs induces a long-term control of skin inflammation despite repeated antigen challenges in presensitized monkeys. No modification in T cell numbers, phenotype, function or metabolism is observed in the peripheral blood or in response to polyclonal stimulation ex vivo. However, long-term in vivo hyporesponsiveness is associated with a significant decrease in the frequency of antigen-specific T cells producing IFN-γ upon antigen restimulation ex vivo. These findings indicate that chronic antigen-specific memory T cell responses can be controlled by anti-IL-7Rα mAbs, promoting and maintaining remission in T-cell mediated chronic inflammatory diseases. Chronic inflammation often involves reactivation of memory adaptive immune. Here the authors show, using non-human primate models, that a single dose of anti-IL-7 receptor monoclonal antibody that exhibits antagonist but not agonist properties can reduce the frequency of antigen-specific T cell to help repress chronic skin inflammation.